Econometric Study of The Impact of Inclusion the Islamic Sukuk in the stock Market on Market Activating in Malaysia during the Period (2001-2019) - Guessoul, Kamel (Finance and Business Economies Review, 2021)
This paper aims to study the impact of inclusion of Islamic sukuk within the financial instruments traded in the stock market on the on market activity in Malaysia during the period of (2001-2019), by exploring these financial instruments and their theoretical role in revitalizing the stock market, to reach in the bezel interaction of market activity with changes in the volume of issuance, where the joint integration test of Angel and Granger was used to study the long-term equilibrium relationship, with the estimation of the error correction model and response functions to determine the error correction factor and the effect of random shocks. this study found a long-term equilibrium relationship between the volume of Islamic sukuk issuance and trading volume as the indicator used to express market activity, and a quick and positive response to trading volume to shocks of the size of sukuk issuance.